Gene amplification of the multidrug resistance 1 gene of Plasmodium vivax isolates from Thailand, Laos, and Myanmar. - Imwong, M; Pukrittayakamee, S; Pongtavornpinyo, W; Nakeesathit, S; Nair, S; Newton, P; Nosten, F; Anderson, T; Dondorp, A; Day, N; White, N (2008)
Plasmodium vivax mdr1 gene amplification, quantified by real-time PCR, was significantly more common on the western Thailand border (6 of 66 samples), where mefloquine pressure has been intense, than elsewhere in southeast Asia (3 of 149; P = 0.02). Five coding mutations in pvmdr1, independent of gene amplification, were also found.